2018
DOI: 10.1016/j.drugalcdep.2018.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Substance use, recovery, and linguistics: The impact of word choice on explicit and implicit bias

Abstract: Results support calls to cease use of the terms "addict", "alcoholic", "opioid addict", and "substance abuser". Additionally, it is suggested that "recurrence of use" and "pharmacotherapy" be used for their overall positive benefits. Both "medication-assisted recovery" and "long-term recovery" are positive terms and can be used when applicable without promoting stigma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
122
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(137 citation statements)
references
References 34 publications
(52 reference statements)
10
122
2
3
Order By: Relevance
“…Topics for such training could focus on encouraging ER staff to use person-first language (e.g., "person with an opioid use disorder") rather than language that increases stigma like "addict". Recent research found that terms like "substance abusers" and "opioid addict" were associated with negative explicit bias (Ashford, Brown, & Curtis, 2018). Building upon those findings, the authors went on to find that stigmatizing terms have the potential to influence medical personnel and their perceptions of individuals with substance use disorders (Ashford, Brown, McDaniel, & Curtis, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Topics for such training could focus on encouraging ER staff to use person-first language (e.g., "person with an opioid use disorder") rather than language that increases stigma like "addict". Recent research found that terms like "substance abusers" and "opioid addict" were associated with negative explicit bias (Ashford, Brown, & Curtis, 2018). Building upon those findings, the authors went on to find that stigmatizing terms have the potential to influence medical personnel and their perceptions of individuals with substance use disorders (Ashford, Brown, McDaniel, & Curtis, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Including visual reminders, such as infographics, to serve as reminders of preferred terms could help create sustainable change within the health care setting. While research cannot yet definitively show that simply using non-stigmatizing language decreases negative explicit and implicit bias (Ashford et al, 2018), efforts to use affirming language in personal and written communications regarding individuals with substance use disorders have the potential to improve the experience for both ER staff and patients.…”
Section: Discussionmentioning
confidence: 99%
“…Even after many trainings and discussions of stigma, people working in the treatment community and health care system still believe that taking medications for opioid use disorder is "substituting one drug for another," and "patients should be tapered from medication as soon as possible." Trainings will continue to emphasize empiricallysupported best treatment practices, address addiction as a chronic disease (McLellan, Lewis, O'Brien, & Kleber, 2000) and use person-first, non-stigmatizing language (Ashford, Brown, & Curtis, 2018) when speaking about substance use disorders.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…For example, local health systems may serve hundreds of thousands of subscribers in urban areas, and the system's policies unquestionably affect the extent to which people seeking care for pain will be stigmatized at various touchpoints in the system. More specifically, language is powerful and plays a large role in conveying stigma against marginalized groups; changing or strengthening local health system policies to reflect appropriate and dignified language in interacting with and caring for people in pain is ethically important 25 . Changing local policies is also significantly easier than altering federal or state policy.…”
Section: Puzzles Of Opioid Use and Policymentioning
confidence: 99%